Does the Sentinel Lymph Node Sampling Alone Improve Quality of Life in Early Cervical Cancer Management? - Gianoni, Martina; Mathevet, Patrice; Uzan, Catherine; Bats, Anne Sophie; Magaud, Laurent; Boutitie, Florent; Lécuru, Fabrice (Frontiers in Surgery, 2020)
Objective: In this subanalysis of the prospective randomized multicenter SENTICOL 2 study, we compared the quality of life (QoL), in two arms, in association with lower-limb consequences in women with early stage cervical cancer undergoing randomized sentinel lymph node (SLN) sampling alone or SLN sampling and full pelvic lymphadenectomy. Methods: 206 patients with an early stage cervical cancer and a negative SLN, were randomized. Every patient had a SLN detection based on a combination of radio-isotope (Nanocis®) and blue dye (Bleu Patenté®) injections. 101 patients, the “standard” group, had complete pelvic lymphadenectomy, 105 patients, the “SLN alone” group, had SLN biopsy without lymphadenectomy. At each visit (V0: preoperative, V1: 1 month, V2: 3 months and V3: 6 months following surgery) the patients completed a Short Form Health Survey (SF36) questionnaire and another questionnaire related to leg lymphedema. SF36 scores variations (compared to the baseline values) were assessed with a standard analysis and by an evaluation of the area under the curve (AUC). Several lower-limb circumferences and signs were also determined. Results: General characteristics of the patients were well balanced between groups. Physical function and general health dimensions of the SF36 scale were significantly improved at V1 and V2 in the “SLN alone” group. Mental health was also statistically better in the “SLN alone” group at V2. Other dimensions were similar. The two groups had similar evaluation at V3. AUC of SF36 sub-scores was also in favor of the “SLN alone” arm, but the difference was not statistically significant. The analysis about the lymphedema of the legs showed a reduced (but not significant) risk in the “SLN alone” group for the top-of-thigh and the mid-thigh perimeters. Lymphedema symptoms reported by the patients were significantly less severe in the “SLN alone” group. Conclusion: Our study demonstrates a trend for a better quality of life and less severe leg heaviness and leg fatigue when a full pelvic lymphadenectomy is avoided.